A system and analytical method for testing the electrical parameters of soil. Issue 1 (30th September 2020) - Han, Yue; Che, Ailan; Feng, Shaokong
Abstract: The electrical parameters of the rock and soil are closely related to the physical parameters. By measuring the resistivity and polarizability of rock and soil reasonably, information on physical parameters such as moisture content, pore ratio and compaction degree can be obtained. A system for testing the electrical parameters of soil samples based on the middle step quadrupole method is developed in this article. The system uses a series of copper needles as the electrodes of the soil-mounted test tube, and uses a multi-point multi-layer test method for layered data acquisition, which can solve the problems caused by the capacitance phenomenon and the heterogeneity of the soil sample. At the same time, factors affecting the test results, such as uneven soil preparation and water addition and electrode disturbance, are regarded as noise. A data-analysis method based on median filtering is proposed to process and analyse the test results, and the relationships between resistivity, polarizability, moisture content and compaction degree of the sample are obtained. The results show that the resistivity decreases nonlinearly as moisture content increases, and the correlation with compaction is not strong; the polarizability increases as moisture content increases with fluctuation, and it first increases and then decreases with an increase in compaction.